Research on DTMF signal detection algorithm for FFT - Tao, Hong (Transactions on Computer Science and Intelligent Systems Research, 2025)
As a signaling method widely used in communication systems (such as telephone buttons and remote control), the core of Dual-tone multi-frequency (DTMF) signal is to represent a key information through the combination of two specific frequency sine waves. In this paper, a detection algorithm based on fast Fourier transform (FFT) is proposed to meet the detection requirements of DTMF signals. The algorithm uses FFT to convert the time-domain signal into a frequency-domain spectrum after preprocessing (filtering and sampling) the acquired DTMF signal, and identifies the row frequency and column frequency components contained in the signal by analyzing the peak frequency in the spectrum, and then maps it to the corresponding key information. Experimental results show that the algorithm can effectively extract the frequency characteristics of DTMF signals, with high detection accuracy and good real-time performance, and can be applied to signal analysis in telephone communication, industrial control and other scenarios.